Towards a Life Cycle Sustainability Assessment method for the quantification and reduction of impacts of buildings life cycle. (August 2019) - Llatas, C; Angulo Fornos, R; Bizcocho, N; Cortés Albalá, I; Falcón Ganfornina, R; Galeana, I; García-Martínez, A; Gómez de Cózar, J C; López Alonso, S; Meda, P; Mercado Martínez, J M; Montes, M V; et al.
Abstract: The construction and building sectors are one of the highest consumers of resources and energy. Literature evidences the potentialities of the design phase towards the improvement of environmental, economic and social performance of buildings. Thus, the Life Cycle Sustainability Assessment (LCSA). approach is recognized as suitable method. It is based on the "triple bottom line" principle, to calculate environmental, economic, social impacts produced by buildings during its life cycle. The present paper aims to present a methodological framework based on an LCSA, used during design stages of buildings and integrated into a building's design technology such as Building Information Modeling (BIM). A conceptual approach to conduct the data integration and a possible workflow to integrate the LCSA into BIM is proposed. The value of the present approach is the possibility to conduct quantitative environmental, economic and social assessment of buildings to guide designers to measure and predict the building's performance.